Do delayed responses introduce bias in ecological momentary assessment? Evidence from comparisons between self-reported and objective physical activity - Stefan Schneider; Stefan Schneider; Stefan Schneider; Meynard J. Toledo; Doerte U. Junghaenel; Doerte U. Junghaenel; Doerte U. Junghaenel; Joshua M. Smyth; Pey-Jiuan Lee; Sarah Goldstein; Olivia Pomeroy; Arthur A. Stone; et al. (Frontiers in Psychology)
IntroductionDelayed responses are a common yet often overlooked aspect of participant compliance in ecological momentary assessment (EMA) research. This study investigated whether response delays introduce selection bias in the moments captured by EMA.MethodsParticipants (n = 339) self-reported their physical activity behaviors using EMA five times a day over 7 days while wearing a continuous physical activity monitor. The continuous activity monitor data provided an objective reference value to evaluate potential biases in delayed EMA self-reports.ResultsResults showed that participants were significantly more likely to delay EMA responses when they were prompted during higher levels of physical activity, and they subsequently reduced their activity levels, postponing their response until they were in a significantly less active state. There was no significant evidence that response delays systematically biased the levels of EMA reported activities, although delayed responses were associated with significantly more random errors in EMA reports (with small effect sizes).DiscussionThe results suggest that respondents self-select the moments for answering EMA surveys based on their current activity levels, but brief response delays do not translate into marked reductions in the quality of EMA data.